Audition : A Memoir - Walters, Barbara 1931- (New York : A.A. Knopf, 2008)
The television journalist chronicles the people, events, and forces that have shaped her life, discussing her relationships with family, friends, and others; her struggle to succeed in a man's world; and the interviews she has conducted during her forty-year career.
Lou, Dena, and my princess grandmother -- My childhood -- "Skinnymalinkydink" -- Sixty-three cents -- The pistachio green house -- New York, New York -- Miami at war -- "A very normal girl" -- Sarah Lawrence -- Television 101 -- Bad choices -- It gets worse -- Television 102 and a strange marriage proposal -- Passage to India -- A funeral and a wedding -- Thirteen weeks to thirteen years -- Becoming Barbara Walters -- Garland, Capote, Rose Kennedy, and Princess Grace -- Born in my heart -- Dean Rusk, Golda Meir, Henry Kissinger, and Prince Philip -- Sad times in Florida -- Winning Nixon, losing Sinatra -- Exit Hugh, enter McGee -- Marriage on the rocks -- Historic journey : China with Nixon -- A dead marriage and the Dead Sea -- Resignation in Washington. Victory in New York -- Fun and games in Washington -- Special men in my life -- Egypt, Israel, and ¡Hola, Castro! -- The million-dollar baby -- "Don't let the bastards get you down" -- Thank heaven! The Specials -- Finally, Fidel -- The historic interview : Anwar Sadat and Menachem Begin -- Exit Harry, enter Hugh -- Heartbreak and a new beginning -- The hardest chapter to write -- 9/11 and nothing else matters -- Presidents and first ladies : forty years inside the White House -- Heads of state : the good, the bad, and the mad -- Adventures with the most mysterious men -- Murderers -- Uncommon criminals -- Over again, never again -- Celebrities who affected my life -- Monica -- The View -- Exit-- To be continued ...
Includes index.
Keywords: Walters, Barbara, -- 1931-; Journalists -- Biography -- United States